Analisis Kinerja Keuangan Pada Bank Pembangunan Daerah (BPD) Kalimantan Timur - Andika Bramudia (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2018)
Andika Bramudia. 2017. Analysis of financial performance at the Regional Development Bank (BPD) of East Kalimantan. Supervised by: Ibu Nurita Affan of    Supervisor and Mrs. Dhina Mustika of    Supervisor.This study aims to determine the financial performance reviewed by Rentability at Regional Development Bank (BPD) of East Kalimantan. The variables used to measure the Financial Performance is the ratio of profitability consisting of Operational Efficiency Ratios, Return On Assets (ROA) and Return On Equity (ROE).The type of data used in this study is secondary data taken from bank financial statements from 2013 to 2016 published by East Kalimantan Regional Development Bank (BPD)The Data analysis technique used is descriptive analysis by using quantitative approach. The analysis is performed on the profitability ratio as well as the comparison from 2013 to 2016.The results of this study, show that the value of operational efficiency ratio, return on asset, and return on equity in 2015 is at the lowest value compared to other years.  Keywords: operational efficiency ratio (REO), return on asset (ROA), return on equity (ROE)